2017
DOI: 10.5152/turkpediatriars.2017.5291
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Candida species and antifungal susceptibilities among children with invasive candidiasis

Abstract: Aim: Non-albicans Candida species and resistant microorganisms have been more commonly isolated in invasive candidiasis in recent years. The aim of this study was to evaluate the distrubution of Candida spp and antifungal resistance in our clinic. Material and Methods: Fifty-four Candida isolates and antifungal susceptibility results obtained from patients diagnosed as having invasive candidiasis between December 2012 and June 2016 were included. Clinical and laboratory data were retrospectively analyzed. E-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
4
12
3
Order By: Relevance
“…19,22,23,28,35 In our study, C albicans was the most common isolate, which is consistent with reports from most other areas worldwide. 19,20,22,25,28,31,[33][34][35] In our study, we found that C glabrata was the second most common Candida species, which is similar to a report from another hospital in China (Liuzhou). 8 Additionally, the distribution of Candida species was similar to that in our report on adult IC in our hospital 36 but different from those in other reports worldwide, such as those from Latin America, 19 England, 25 Turkey, 22,31 Canada, 33 the United States, 33 Iran, 20 China (Taiwan) 28 and Brazil.…”
Section: Among Neonates With Invasivesupporting
confidence: 91%
See 2 more Smart Citations
“…19,22,23,28,35 In our study, C albicans was the most common isolate, which is consistent with reports from most other areas worldwide. 19,20,22,25,28,31,[33][34][35] In our study, we found that C glabrata was the second most common Candida species, which is similar to a report from another hospital in China (Liuzhou). 8 Additionally, the distribution of Candida species was similar to that in our report on adult IC in our hospital 36 but different from those in other reports worldwide, such as those from Latin America, 19 England, 25 Turkey, 22,31 Canada, 33 the United States, 33 Iran, 20 China (Taiwan) 28 and Brazil.…”
Section: Among Neonates With Invasivesupporting
confidence: 91%
“…Regarding resistance, our study showed that the ITR resistance rate was the highest at 26.7% for all Candida species, followed by VRC (14.0%), FCA (8.1%) and 5-FC (2.3%); none of the isolates in this study were resistant to AMB. The ITR resistance rate was higher than those reported by Tragiannidis et al, 18 Tsai et al 37 and Sutcu et al 31 and consistent with that in Hsu et al's 28 report. The VRC resistance rate was higher than that reported by Tsai et al 37 and consistent with that in Sutcu et al's 31 report.…”
Section: Ta B L E 4 Factors Associated With 60-d Mortality By Multivasupporting
confidence: 86%
See 1 more Smart Citation
“…In a single-institution study from Istanbul, C. albicans and NAC species were equally distributed as the causative agent of invasive candidiasis among children aged 0-18 years of age. 25 However, in a prospective, international, epidemiologic study of invasive candidiasis in children and neonates that enrolled 196 children and 25 neonates from 2007 to 2011, NAC species predominated in both children (56%) and neonates (52%). 26 In the PATH database, candidemia was caused by NAC species in 54.4% of the cases.…”
Section: S Hif T From C Alb Ic Ans To Non -Alb Ic Ans C Andida S mentioning
confidence: 99%
“…Regarding cases of resistance to AB, two other non-albicans strains also derived from invasive candidiasis were resistant to this polyene [31]. In light of the current information, the molecular mechanisms of resistance to this antifungal drug, which are strictly related to the failure in treatment of these invasive fungal infections, are highlighted [32,33].…”
Section: Discussionmentioning
confidence: 97%